Assessment of Organochlorine pesticides in cocoa beans from Ashanti and Brong Ahafo regions of Ghana - S, Boakye,; Essien W, Jonfia-; B.R, Voegborlo,; N,O, Boadi (IJRDO-Journal of Applied Science, 2016)
Research was conducted in the Ashanti and Brong Ahafo regions of Ghana to determineorganochlorine pesticide residues in cocoa beans. The pesticides were extracted by using solventextraction technique followed by clean up with C-18 and Envi – Carb NH2 solid-phase extractioncartridges. Extracts were dissolved in ethyl acetate and analysis carried out by GasChromatograph equipped with Electron Capture Detector. Retention times were used foridentification of pesticides and quantified using external calibration method. From this study,55.5 % of cocoa beans sampled from Brong Ahafo region and 66.7 % of cocoa beans sampledfrom the Ashanti region had organochlorine pesticide residue concentrations above the EUpermissible levels. Heptachlor had the maximum concentration of residues whilst heptachlor exoepoxide had the minimum concentration for the two regions. The results obtained reflect theenormous past use and continual usage of pesticides on cocoa beans in Ghana.